High tolerance to extreme environment: the case of a catfish in Rawog - A. H. Ahmad; Hairul Hafiz Mahsol (Sabah Forestry Department, 2019)
Some of tropical freshwater fish are able to tolerate very low dissolved oxygen and over a range of acidity. Natural habitats provide a wide range of ecological settings allowing for specialists that could live in the different microhabitats, hence reducing competition. Sluggish and small waterways and stagnant ponds in around the Sg. Rawog Conservation Area were examined for the presence of freshwater fishes. The values for acidity and dissolved oxygen from each station were recorded. We report here the different levels of tolerance of freshwater fish species against acidity and dissolved oxygen, with a species of catfish being the only species found in the stagnant black water ponds.